Senior playgrounds in the promotion of physical activity among the elderly: characteristics of use - Bettencourt, Liliana (2016)
The aim of this study is to analyse the behaviour of users of senior playgrounds (SP) and chart their profile. The methodology used was non-participant observation. The sample consisted of 129 users of SP present in the various moments of observation. The results indicate an increasing number of children and adults and a larger number of users on weekends. The duration of usage varied between 1 and 30 minutes and the most widely used pieces of equipment were surfing and ski. Despite the fact that SP are designed for the elderly, it seems that these do not use it much.